Understanding physical environment through safe highway transport mobility with special review on climate - the highway route Belgrade - Novi Sad, Serbia - Sentić, Ivana; Đorđević, Tijana (Geographica Pannonica, 2019)
This paper focuses on the highway corridor Belgrade-Novi Sad, Serbia and the relationship between the highway and surrounding nature, as an integral part of the spatial entity which the highway belongs to. The paper emphasizes a high importance of studying the physical-geographical factors in the process of highway construction in order to achieve high level of traffic safety. Particular attention was directed to climate elements – the factors that are not so visible, but still may pose a great risk to road safety. Data were taken from CARPATCLIM database and their evaluation was confirmed by the data obtained from CHEK-LISTS. It was found that the climate elements have a strong influence, but it can be successfully controlled by vegetation. Landscape design of both sides of the highway may offer a possibility of mitigating the influence of climate elements, which was also pointed out in the paper.